2022
DOI: 10.1073/pnas.2208662119
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of lipoprotein recognition by the bacterial Lol trafficking chaperone LolA

Abstract: In gram-negative bacteria, lipoproteins are vital structural components of the outer membrane (OM) and crucial elements of machineries central to the physiology of the cell envelope. A dedicated apparatus, the Lol system, is required for the correct localization of OM lipoproteins and is essential for viability. The periplasmic chaperone LolA is central to this trafficking pathway, accepting triacylated lipoproteins from the inner membrane transporter LolCDE, before carrying them across the periplasm to the OM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 61 publications
1
16
0
Order By: Relevance
“…The Nterminal helix, α1, forms the oor of the cleft. The non-polar cleft can interact either with the periplasmic loop of LolC, when uncharged, or the acyl chains of a lipoprotein during protein transportation [18,20]. The helical segment that lls the hydrophobic cavity is comprised of 22 aa in both LolA-PG and LolA-VC but the different position of the helices results in different accessibility to the clefts.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Nterminal helix, α1, forms the oor of the cleft. The non-polar cleft can interact either with the periplasmic loop of LolC, when uncharged, or the acyl chains of a lipoprotein during protein transportation [18,20]. The helical segment that lls the hydrophobic cavity is comprised of 22 aa in both LolA-PG and LolA-VC but the different position of the helices results in different accessibility to the clefts.…”
Section: Resultsmentioning
confidence: 99%
“…5b). In in vitro assays it was shown that these compounds induce release of lipoproteins from LolA [20] whereas it is claimed that in vivo targets of these compounds are not LolA or LolB but instead the Mre system [33]. In this study we used ITC to clarify if A22 interacts with recombinant LolA or LolB, when they are not charged with lipoproteins.…”
Section: The Interaction Between Lola and Lolbmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings further underpin the assignment of LolCDE into the group of type VII ABC transporters, as MacB is the founding member of this group [ 24 ]. In a more recent study, the crystal structure of LolA bound to a ligand was also solved by the Koronakis lab [ 150 ]. The structure shows the precise interaction of the acyl chains of the lipoprotein with the hydrophobic cavity in LolA.…”
Section: The Lol Systemmentioning
confidence: 99%
“…Additionally, LolA from E. coli (LolA-EC) has also been studied in complex with LolC both using crystallography and cryo-electron microscopy 18 , 19 . These studies were recently supplemented with the X-ray structure of E. coli LolA in complex with a triacylated peptide 20 . Comparatively, LolB, which serves as an attractive drug target against Vibrio parahaemolyticus 21 , is less studied, with only the E. coli crystal structure being published 17 .…”
Section: Introductionmentioning
confidence: 99%